2008
DOI: 10.1016/j.rmed.2007.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant treatment with nebulized formoterol and tiotropium in subjects with COPD: A placebo-controlled trial

Abstract: Adding a long-acting beta(2)-agonist (LABA) by dry powder inhaler (DPI) to tiotropium provides significantly increased and sustained bronchodilation in chronic obstructive pulmonary disease (COPD) patients over either product alone. To demonstrate similar benefits with a nebulized LABA, a placebo-controlled trial was conducted to evaluate the efficacy and safety of formoterol fumarate inhalation solution in subjects receiving tiotropium as a maintenance treatment for COPD. After a 7-14-day screening period usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 32 publications
7
57
0
5
Order By: Relevance
“…71 Further benefits were seen when other drugs were added to tiotropium therapy -for example, with the addition of salmeterol 66 but not with formoterol. 67,69 Comparisons of tiotropium monotherapy with triple therapy (tiotropium plus two other therapies) showed the potential clinical advantages of this latter approach to treatment. 66,68,72 It should be noted that, while the UPLIFT ® trial compared tiotropium monotherapy to placebo (control), its study design means that the comparison was made in the context of a background of "any other respiratory medication".…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…71 Further benefits were seen when other drugs were added to tiotropium therapy -for example, with the addition of salmeterol 66 but not with formoterol. 67,69 Comparisons of tiotropium monotherapy with triple therapy (tiotropium plus two other therapies) showed the potential clinical advantages of this latter approach to treatment. 66,68,72 It should be noted that, while the UPLIFT ® trial compared tiotropium monotherapy to placebo (control), its study design means that the comparison was made in the context of a background of "any other respiratory medication".…”
Section: Discussionmentioning
confidence: 99%
“…66 The addition of formoterol fumarate (a LABA) to tiotropium resulted in little benefit over tiotropium monotherapy in terms of SGRQ in two 6-week studies. 67,69 The only (clinically and statistically) significant change was observed in the symptom score for dual therapy versus monotherapy in one study. 69 In terms of TDI scores, there was a significantly greater improvement with dual therapy in one trial 69 but not the other; 67 more patients had improvements in dyspnoea in the dual therapy versus monotherapy group in both studies.…”
Section: Tiotropium Versus Tiotropium Plus Another Agent (Dual Therapy)mentioning
confidence: 95%
See 1 more Smart Citation
“…The proportion of patients achieving the MCID in TDI total score was 31.1-57.1% for tiotropium monotherapy, 48.0-66.7% for LABA monotherapy, and 57.7-77.9% for LABA/LAMA combination therapy. 17,19,20,22 Overall, LABA/LAMA combination therapy demonstrated clinically relevant improvements in dyspnoea, greater than those seen with LABA or tiotropium alone. …”
Section: Dyspnoeamentioning
confidence: 90%
“…All studies of tiotropium and formoterol/arformoterol combination therapy improved dyspnoea (assessed by the Transitional Dyspnoea Index (TDI)) to a greater extent than either monotherapy. 6,[15][16][17]19,20 Two further studies of tiotropium plus salmeterol (once or twice a day) also showed a marked improvement in dyspnoea with combination therapy over either monotherapy. 21,22 In a study by Aaron et al, 7 no significant difference in mean TDI total score was demonstrated between tiotropium plus salmeterol, tiotropium plus salmeterol/ fluticasone and tiotropium alone; however, it should be noted that a large number of patients discontinued during this study (61.0% completed), making it difficult to draw firm conclusions on efficacy between treatment groups.…”
Section: Dyspnoeamentioning
confidence: 95%